Discours d’enseignants sur la diversité linguistique et culturelle dans leurs classes : quels apports pour la formation ? - Vera Delorme; Małgorzata Jaskuła (Recherches en didactique des langues et des cultures)
This article proposes to question teachers’ representations of the linguistic and cultural diversity present in their classes, and more generally of education for plurality. The representations system integrated into the didactic repertoire of a practitioner can directly influence a professional practice. The objective of our article is to highlight the impact of the representations that teachers have of plurilingualism, otherness and cultural and linguistic groups on their actions in the classroom. The corpus of the study uses 23 writings of primary and secondary school teachers produced for training course in teaching French as a second language. The analysis made possible to raise the representations in question, their influence on practices as well as indices of change. Finally, we propose some possible ways of integrating the results of our research into design of teacher trainings.